Damage Study of Irradiated Tungsten using fast focus mode of a 2.2 kJ plasma focus - Damideh, Vahid*; Lee, S.*; Saw, S. H.; Jalil, Ali; Rawat, R. S.; Lee, P. (Elsevier, 2017)
In this work, damage results of four 12 mm × 12 mm × 5 mm PLANSEE double forged tungsten target samples exposed in INTI PF device at different distances from anode operating in the fast focus mode at 12 kV, 2.5 Torr deuterium are presented. SEM and EDX images and analysis show the extent of damage on the exposed tungsten surface. Micro-cracks up to 300 nm and 500 nm to 5 μm holes together with signs of melting are found on the tungsten exposed surfaces depending on their distances from the anode top. Current waveforms fitting using Lee Model Code show yields of 3 × 106 neutrons and 8.5 × 1014 ions per shot with average ion energy of 56 keV per ion at pinch exit, generating heat flux of 1.8 × 1014 Wm−2 and damage factor (also called heat flux factor) of 1.6 × 1010 Wm−2s0.5 on a target at pinch exit.